Indoor positioning and orientating system based on visible light communication - Guowei YANG; Zhaobiao HUANG; Bing FAN; Xuefang ZHOU; Meihua BI (Tongxin xuebao)
For the insufficient research on the simultaneously positioning and orientating system, a VLC positioning and orientating algorithm based on combining particle swarm optimization (PSO) and beetle antennae search (BAS) was proposed.The PSO algorithm was used to explore the optimal direction of the receiver and meanwhile the BAS algorithm was used to search the best three-dimensional coordinates of each particle in the current direction.Firstly, the indoor space of 3 m×3 m×5 m and the SNR of 40 dB were assumed in the simulation, the proposed VLC indoor positioning and orientating system could achieve the average positioning error of 4.82 cm and average orientating error of 2.24°.Then, in the laboratory space of 0.9 m×0.9 m×1.5 m, the experimental demonstration was accomplished for the first time, and the average positioning and orientating errors of this experimental system were 5.32 cm and 5.99°, respectively.Compared with the traditional VLC indoor positioning schemes, the proposed VLC positioning and orientating system does not need the prior knowledge of the height and direction of the receiver, which greatly reduces the system complexity and is applicable to a wider range of applications.